2010
DOI: 10.1111/j.1439-0426.2009.01377.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between gonad development and sex steroid levels at different ages inAcipenser schrenckii

Abstract: The histological developments of the gonad and the associated sex steroid levels were determined in the breeding stocks of Acipenser schrenckii (age classes 1 to 5) maintained under natural temperature regimes (December 4°C; August 26°C). Early sex differentiation was observed in 1-year-old fish, while testosterone (T) and 17b-estradiol (E 2 ) levels ranged from T 1.1 to 3.4 nmol l )1 (average 1.8 nmol l )1 ), and E 2 varied from 24 to 85 pmol l )1 (av. 50.3 pmol l )1 ). Gonadal status of 2-year-old males was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Yet, in comparison with the above‐stated technique, cross‐sectional image approach has shown to be useful to distinguish developmental stages (Wildhaber et al., ). Our staging designations are similar to those described on different sturgeon species (Doroshov et al., ; Flynn & Benfey, ; Matsche et al., ; Qu et al., ). As shown in previous studies, histological and hormonal assessments have been used as reliable methods to provide a complete staging description correspond to different seasons (Doroshov et al., ; Matsche et al., ).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Yet, in comparison with the above‐stated technique, cross‐sectional image approach has shown to be useful to distinguish developmental stages (Wildhaber et al., ). Our staging designations are similar to those described on different sturgeon species (Doroshov et al., ; Flynn & Benfey, ; Matsche et al., ; Qu et al., ). As shown in previous studies, histological and hormonal assessments have been used as reliable methods to provide a complete staging description correspond to different seasons (Doroshov et al., ; Matsche et al., ).…”
Section: Discussionmentioning
confidence: 67%
“…Study of sex steroid levels in serum provided new information on the gonadal steroidogenic capacity of sturgeon, and may serve as the basis for further studies on the hormonal control of male and female gonadal development in these fish (Amiri et al., ). It has been shown that gonad development at all stages in sturgeon is influenced by sex steroid hormones (Qu et al., ). In the present study, sterlet sturgeon males showed that serum 11‐KT levels were relatively low in resting phase at the spermatogonial proliferation stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gonadal development stages were examined according to ultrasound images or histological studies (19) . For histological observation, gonad samples were sectioned at 5 μm and stained with haematoxylin-eosin (28) . Muscle samples were sectioned at 8 μm and stained with oil-red O.…”
Section: Sample Analysismentioning
confidence: 99%
“…Serum levels of E 2 decreased from January to July in our study. The E 2 level in Amur sturgeon Acipenser schrenckii was low at early stages of maturity and increased towards the final maturation (Qu et al., ). E 2 in shovelnose sturgeon Scaphirhynchus platorynchus at the previtellogenic stage was 34.8 pg ml −1 , ranging from 0.5 to 500 pg ml −1 (Wildhaber et al., ).…”
Section: Discussionmentioning
confidence: 99%